Socialization of Prevention of Child Marriage in Jenggala Village, Tanjung District, North Lombok Regency - wati, Fahmi; Musafir, Musafir; Habiburrahman, Habiburrahman; Hidayati, Ismi; Ipadah, Ipadah; Hartini, Susi; Sukur, Sukur (Abdi Masyarakat, 2024)
Child marriage is increasing in North Lombok Regency and has attracted a lot of government attention because it has a major impact on the progress of the nation. The many cases of child marriage, one of which occurred in Jenggala Village based on data obtained from the Jenggala Village government, there were 7 cases of child marriage originating from 5 Hamlets in Jenggala Village, with assistance that has been carried out by LPAI and the Village government, two of the 7 cases that occurred received compensation from the government. One of the efforts to reduce cases of child marriage is by collaborating with educational institutions, through community service activities or KKN. In this community service activity, the goal to be achieved is to raise awareness and reduce the number of child marriages in Jenggala Village, Tanjung District, North Lombok Regency. The subjects of the activity were teenagers from 9 Hamlets in Jenggala Village. The methods of observation, counseling and documentation. The results of this child marriage prevention socialization activity received a response and enthusiasm from the community who participated in the activity, originating from 9 Hamlets in Jenggala Village. This condition is expected to be able to foster concern, knowledge, and involvement of adolescents in voicing and avoiding child marriage.